Il diritto internazionale come “motore” del biodiritto e l’emersione di un “biodiritto internazionale” (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Since the adoption of the Nuremberg code, at the end of the Nazi doctors’ trial, international law has contributed to the development of biolaw. While international human rights standards orientate domestic legal system in regulating life sciences and biomedicine in particular, a specific corpus of international law norms and principles is constantly growing, attesting the perceived need for an intergovernmental effort to deal with challenges posed by scientific progress.
Keywords: International law; human rights; bioethics; international biolaw; soft law